Pengaruh Penggunaan Media Sosial Twitter Terhadap Pemenuhan Kebutuhan Informasi (Survei Terhadap Pengikut Akun @Habisnontonfilm) - Putri, Dwi Irenniza Aulia; Saputra, Faisal Tomi; Hardiyanti, Rini (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is entitled "The Effect of Using Twitter Social Media on Fulfilling Information Needs (Survey of Followers @HabisNontonFilm). The formulation of the problem to be discussed in this study is to determine the influence between the use of twitter social media on the fulfillment of followers' information needs. The aim is to explain whether there is an influence on the use of social media twitter @HabisNontonFilm on the fulfillment of information needs in followers. the theory used is the theory of uses and gratification. The method used is a quantitative method using a sampling technique with purposive sampling technique. The results showed that the use of social media had a positive and significant effect on information needs. Based on the results of the coefficient of determination test, it is found that the use of media (X) affects the need for information (Y) by 51.8%, while the remaining 48.2% is influenced by other factors not examined in this study.